If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x+8)=10x+2x+32
We move all terms to the left:
4(3x+8)-(10x+2x+32)=0
We add all the numbers together, and all the variables
4(3x+8)-(12x+32)=0
We multiply parentheses
12x-(12x+32)+32=0
We get rid of parentheses
12x-12x-32+32=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 33+114+3a=180 | | -3x+8x-67=78 | | 3x-19=61 | | 2x+1(2x-17)=86 | | 2x+15=3x+15=180 | | -4a+2=6a+12 | | m1°=21,m2° | | 82-0.4x=82 | | 2(n-4)=-3n-12 | | 4/z-1=8/6 | | x-6=40=-8(x+8) | | 111=3(1-5x)+3 | | 7/9x-23=33 | | k+1.4=7.8 | | 5-3y=-25 | | Y-5=-3(x-10) | | 2x+15=3x+15=90 | | x+5+3x+5=75 | | 10d-12=4+2d | | 3.4x=16 | | 3-5m=-22 | | 5x+45=5x+100/2 | | -12+2n=3n+3n | | 2c-5=53 | | j-6-6=-1-6 | | 17-4h=-2h-17 | | 2d–15=3 | | 9=2(x+7)-7x | | x/13=12/26 | | -2x+5-4x-1x=12 | | 21=5n+2n | | 30=6x+54 |